2020
DOI: 10.1007/s12671-020-01555-8
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of Mindfulness Facets, Affect, Compassion, and Distress

Abstract: Objectives Mindfulness, positive affect, and compassion may protect against psychological distress but there is lack of understanding about the ways in which these factors are linked to mental health. Network analysis is a statistical method used to investigate complex associations among constructs in a single network and is particularly suitable for this purpose. The aim of this study was to explore how mindfulness facets, affect, and compassion were linked to psychological distress using networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 66 publications
5
23
0
Order By: Relevance
“…Of note, like the two previous network studies comprising the five facets 41 , 42 , there was no direct association between Acting with Awareness and Non-Reactivity. As suggested Medvedev and colleagues 41 , these two facets might act as bridges between the facets and maladaptive factors such as depression and negative affect, by prompting responding to external and internal stressors through acting with awareness and allowing unpleasant thoughts, feelings, and sensations to come and go without reacting to them. A future step will thus be to capitalize on temporal network analyses from intensive longitudinal research designs to further elucidate the role of these two facets.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Of note, like the two previous network studies comprising the five facets 41 , 42 , there was no direct association between Acting with Awareness and Non-Reactivity. As suggested Medvedev and colleagues 41 , these two facets might act as bridges between the facets and maladaptive factors such as depression and negative affect, by prompting responding to external and internal stressors through acting with awareness and allowing unpleasant thoughts, feelings, and sensations to come and go without reacting to them. A future step will thus be to capitalize on temporal network analyses from intensive longitudinal research designs to further elucidate the role of these two facets.…”
Section: Discussionsupporting
confidence: 60%
“…With regard to mindfulness, only two studies thus far have applied a network analytic framework to examine the interdependence between the five facets of mindfulness, and these studies specifically focused on the relations of the facets with other clinical psychological constructs 41 , 42 . In one study, Medvedev and colleagues 41 examined the relations between the facets of mindfulness, compassion, positive and negative affect, and psychological distress. They found that Non-judging was inversely related to all aspects of psychological distress, whereas Non-reactivity and Acting with Awareness acted as bridges between protective and maladaptive factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous studies have found that compassion training may not reduce negative affect (Engen & Singer, 2015;Klimecki et al, 2013Klimecki et al, , 2014 and that dispositional compassion for others' suffering may not associate with negative affect in questionnaire-based studies (Arimitsu et al, 2019;López et al, 2018;Medvedev et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…To the best of our knowledge, no study has investigated the relationship of compassion and vital exhaustion. Regarding negative affect, three studies have found that dispositional compassion for others' suffering may not associate with negative affect (Arimitsu et al, 2019;López et al, 2018;Medvedev et al, 2020).…”
Section: Introductionmentioning
confidence: 99%